2014
DOI: 10.12983/ijsres-2014-p0228-0232
|View full text |Cite
|
Sign up to set email alerts
|

Change of Electrokinetic Potential Value of Rat Blood Erythrocytes Irradiated by EMI EHF

Abstract: Abstract. The change of electrokinetic potential (-potential) value of erythrocytes in rat blood has been studied under the influence of electromagnetic irradiation with 41.8 GHz and 42.2 GHz frequencies. It was shown that this physical field with the mentioned frequencies effects on the organisms compared to non-irradiated control ones. Moreover the multiple effect results in more obvious changes of erythrocyte -potential value which indicates that cumulative effect of the factor is observed. It was also sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…We have shown that EMI in millimeter range (MM) affect albumin, invoking the certain conformational reconstructions in its dimensional structure [8]. As it was shown MM EMI affect not only proteins, but also whole cell, resulting in changes of electrokinetic potential of erythrocytes of rat blood [9].…”
mentioning
confidence: 99%
“…We have shown that EMI in millimeter range (MM) affect albumin, invoking the certain conformational reconstructions in its dimensional structure [8]. As it was shown MM EMI affect not only proteins, but also whole cell, resulting in changes of electrokinetic potential of erythrocytes of rat blood [9].…”
mentioning
confidence: 99%